Serine phosphorylation facilitates protein degradation by the human mitochondrial ClpXP protease - Yue Feng; Monica M. Goncalves; Yulia Jitkova; Alexander F. A. Keszei; Yongran Yan; Chaitra Sarathy; Jonathan St-Germain; Tristan M. G. Kenney; Matthew Tcheng; Vincent Trudel; Ross S. Mancini; Rahul Upadhyay; et al. (Proceedings of the National Academy of Sciences, 2025)
ClpXP is a two-component mitochondrial matrix protease. The caseinolytic mitochondrial matrix peptidase chaperone subunit X (ClpX) recognizes and translocates protein substrates into the degradation chamber of the caseinolytic protease P (ClpP) for proteolysis. ClpXP degrades damaged respiratory chain proteins and is necessary for cancer cell survival. Despite the critical role of ClpXP in mitochondrial protein quality control, the specific degrons, or modifications that tag substrate proteins for degradation by human ClpXP, are still unknown. We demonstrated that phosphorylated serine (pSer) targets substrates to ClpX and facilitates their degradation by ClpXP in biochemical assays. In contrast, ClpP hyperactivated by the small-molecule drug ONC201 lost the preference for phosphorylated substrates. Hydrogen deuterium exchange mass spectrometry combined with biochemical assays showed that pSer binds the RKL loop of ClpX. ClpX variants with substitutions in the RKL loop failed to recognize phosphorylated substrates. In intact cells, ClpXP also preferentially degraded substrates with pSer. Moreover, ClpX substrates with the pSer were selectively found in aggregated mitochondrial proteins. Our work uncovers a mechanism for substrate recognition by ClpXP, with implications for targeting acute myeloid leukemia and other disorders involving ClpXP dysfunction.